Educational Significance Of Works Recommended For Reading To Teenage Girls - Kochkarova Aysha Oltibayevna; Ulmasova Mehrangiz Ashrafovna (Zien Journals, 2024)
The Uzbek people are one of the ancient Turkic peoples with a long history and rich cultural heritage. We can see that our people pay special attention to the education of girls and their education, and we can see from the conditions created for them to read books from their teenage years.
Keywords: reading; cultural heritage; monument